A biomechanical model for concomitant functioning of neck and shoulder: a pilot study - Alexandra Yurova; Andrey Gladkov; Eugene Kalinsky; Alexey Lychagin; Anatoly Shipilov; Yuri Vassilevski (Scientific Reports)
Abstract A combination of pain syndromes in the neck and shoulder joints creates a significant burden on the healthcare system and has important social and economic significance. Treatment of these pathologies is often inefficient and can reduce the quality of life for patients. Studying of the relationship between pathological changes in the cervical spine and diseases of the shoulder area is crucial for developing more efficient treatment methods. Biomechanical modeling can be a valuable tool in this research, as assessing muscle function in patients is not always feasible. To our knowledge, there are no open-source biomechanical models for concomitant functioning of neck and shoulder. The aim of this research is to construct a biomechanical model for neck and shoulder concomitant functioning and to investigate numerically the work of neck and shoulder muscles during head and arm movements.